Learner Support in Distance Education: Unlocking the Potential of Public Libraries in Supporting Teaching and Learning In Open and Distance Learning - Nabushawo, Harriet; Aguti, Jessica Norah; Winterbottom, Mark (In EDEN Conference Proceedings, 2015)
This study examined the nature of services and facilities available and accessible in public libraries to ODL students in sub-Saharan Africa and the challenges these services face. Library services are central in teaching and learning processes because they expose the students to a variety of resources which facilitate in-depth study and lead to development of intended competencies. However, according to Pernell (2002), traditional library services often fail to adapt to the needs of Open and Distance Learning students especially in dual mode universities. This in the end affects students' final grades as well as the quality of education they receive. Using a cross sectional survey, from 422 respondents who include students, staff (both on campus and off campus) and librarians, data were collected though questionnaires, interviews, focus group discussions and documentary analysis. The findings reveal that due to inadequate library resources in study centres where ODL students are meant to receive remote support, the students have been utilizing library resources from the public libraries. This support from public libraries however needs to be acknowledged and fully integrated in the University policy provision for effective collaboration and knowledge sharing to ensure smooth coordination of library activities. This paper seeks to examine the potential of public libraries in supporting distance learners in Makerere University and the need for policy to guide the collaborations and while sharing library resources.